Comparison of Pulsatility Index and Notching of Uterine Artery Doppler on Normotensive Pregnancy and Established Pre-eclampsia - Utomo, Muhammad Wahyu; Nurdiati, Detty Siti; Rachman, Irwan Taufiqur; Kusuma, Raden Aditya (Indonesian Journal of Obstetrics and Gynecology, 2025)
Objective: The aim was to assess pulsatility index of uterine artery (Ut-A PI) of normotensive pregnancy and preeclampsia between 28-40 weeks of gestation. Methods: This cross-sectional study was conducted at Dr. Sardjito Hospital and Harapan Kita Maternal Children Hospital as a tertiary referral hospital. The study included 220 women high risk pregnancies. Result: There were 188 pregnant women normotensive pregnancy (85.5%) and 32 preeclampsia cases (14.5%). Weight, Body Mass Index, blood pressure, Mean Arterial Pressure, chronic hypertension, history of preeclampsia, and baby weight showed an significant association with preeclampsia. Pulsatility index of uterine artery had a sensitivity of 87.50% and a specificity of 98.94% whereas the notching had a sensitivity of 46.88% and a specificity of 87.23%. Conclusion: The UtA PI is a complementary tool with good performance for the diagnosis of overall and severe preeclampsia with high sensitivity and specificity. UtA PI has better performance the notching. Keywords: Pulsatility index, notching, normotensive, preeclampsia